IN THE JEWELRY, BRAZING AND LASER WELDING WITH PARAMETER OPTIMIZATION - GÜLLÜOĞLU, ARİF NİHAT (POLSKA AKAD NAUK, POLISH ACAD SCIENCES, INST METALL & MATER SCI PAS, 2012)
In this study, brazing and laser welding were experimentally compared for 9, 14 and 18 carat gold alloys in different color. The gold alloys were joined by laser welding and brazing and the microstructure, hardness, chemical composition, color of the weld joints were investigated. According to study, in laser welding, voltage, pulse duration, pulse diameter and frequency are the most important welding parameters that influence the quality of joints. Welded joints are characterized using three geometric parameters: penetration depth, width of heat affected zone and underfill defects. Finally, optimum laser welding parameters of different color of 9, 14 and 18 carat gold alloys were determined. It is observed that laser welding has numerous advantages compared to the other joining techniques used in the jewelry industry.
Keywords: laser welding; brazing; jewelry; gold alloys; carat; ALLOY